Economic impacts of Tourism on tourism service providers worldwide: A systematic review - Condori Chura, Delia (2023)
Tourism is an economic activity with both positive and negative impacts on society. This study focused on analyzing the economic impacts of tourism on tourism service providers worldwide. A comprehensive search for scientific papers was conducted in databases such as Scopus, Web of Science, and Dialnet, resulting in 89 articles, of which 12 were selected for review. The findings revealed highly positive impacts on tourism service businesses, such as accommodations, restaurants, leisure centers, camps, and tour operators. Additionally, microeconomic-level enterprises were highlighted as beneficiaries. In conclusion, tourism significantly contributes to the generation of local economic benefits. However, current global trends demand that the tourism industry focuses on principles of equity, responsibility, and respect. When properly managed, tourism becomes a dynamic driver of the economy at both local and global levels.